Astragalus membranaceus and its monomers treat peritoneal fibrosis and related muscle atrophy through the AR/TGF-β1 pathway - Sheng, Li; Sun, Jinyi; Huang, Liyan; Yu, Manshu; Meng, Xiaohui; Shan, Yun; Dai, Huibo; Wang, Funing; Shi, Jun; Sheng, Meixiao (Frontiers in Pharmacology, 2024)
Backgroud: To anticipate the potential molecular mechanism of Astragalus membranaceus (AM) and its monomer, Calycosin, against peritoneal fibrosis (PF) and related muscle atrophy using mRNA-seq, network pharmacology, and serum pharmacochemistry.Methods: Animal tissues were examined to evaluate a CKD-PF mice model construction. mRNA sequencing was performed to find differential targets. The core target genes of AM against PF were screened through network pharmacology analysis, and CKD-PF mice models were given high-and low-dose AM to verify common genes. Serum pharmacochemistry was conducted to clarify which components of AM can enter the blood circulation, and the selected monomer was further validated through cell experiments for the effect on PF and mesothelial mesenchymal transition (MMT) of peritoneal mesothelial cells (PMCs).Results: The CKD-PF mice models were successfully constructed. A total of 31,184 genes were detected in the blank and CKD-PF groups, and 228 transcription factors had significant differences between the groups. Combined with network pharmacology analysis, a total of 228 AM-PF-related targets were identified. Androgen receptor (AR) was the remarkable transcription factor involved in regulating transforming growth factor-β1 (TGF-β1). AM may be involved in regulating the AR/TGF-β1 signaling pathway and may alleviate peritoneal dialysis-related fibrosis and muscle atrophy in CKD-PF mice. In 3% peritoneal dialysis solution-stimulated HMrSV5 cells, AR expression levels were dramatically reduced, whereas TGF-β1/p-smads expression levels were considerably increased.Conclusions: AM could ameliorate PF and related muscle atrophy via the co-target AR and modulated AR/TGF-β1 pathway. Calycosin, a monomer of AM, could partially reverse PMC MMT via the AR/TGF-β1/smads pathway. This study explored the traditional Chinese medicine theory of "same treatment for different diseases," and supplied the pharmacological evidence of "AM can treat flaccidity syndrome.